2017
DOI: 10.1111/iej.12789
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium oxide and niobium oxide used as radiopacifiers in a calcium silicate‐based material stimulate fibroblast proliferation and collagen formation

Abstract: The experimental materials (CS + ZrO and CS + Nb O ) induced fibroblast proliferation and accelerated the regression of the inflammatory reaction. However, the addition of nanoparticulate radiopacifiers did not improve the biological properties of a calcium silicate-based cement when compared to microparticulate agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…, Silva et al . ). In the present study, a concomitant presence of FGF‐1‐positive cells and Ki‐67‐labelled cells was observed in the capsules of both calcium silicate materials and in the control group, reinforcing the concept that FGF‐1 stimulates mitotic activity (Zakrzewska et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…, Silva et al . ). In the present study, a concomitant presence of FGF‐1‐positive cells and Ki‐67‐labelled cells was observed in the capsules of both calcium silicate materials and in the control group, reinforcing the concept that FGF‐1 stimulates mitotic activity (Zakrzewska et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Silva et al . ). The greatest immunoexpression for FGF‐1 accompanied by accentuated Ki‐67‐immunolabelled cells found at 7 days indicates that FGF‐1 may have stimulated fibroblast proliferation, explaining the significant and gradual increase of these cells in all groups.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The coordinate action of these chemokines regulates the degree of the inflammatory reaction as well as its regression and tissue repair 5 . A biocompatible material may allow the release of mediators by host cells which promote the regression of the inflammatory reaction 4,18,[20][21][22] and stimulate the tissue repair 5,22 . Among the cytokines and growth factors, the interleukin-6 (IL-6) has a participation in the initiation and maintenance of the inflammatory reaction 4,5,[23][24][25] .…”
mentioning
confidence: 99%